Metal Decorations of Door of Saheb al-Amr Mosque in Tabriz: Azerbaijan Folk Art from Qajar Era - Mohammadizadeh, Akram; Marasy, Mohsen (Journal of History Culture and Art Research, 2019)
Mosques play a significant role in the lives of Muslims in addition to acting as places of worship. One of the most significant mosques of Azerbaijan region of Iran is Saheb al-Amr Mosque in Tabriz City. The mosque has unique designs of masks, metal hands and praying tablets made of metallic plates which were installed on the mosque door. Considering the inhibition of using portraiture in mosques and holy places, the present study intends to review the technical and artistic qualities as well as reasons behind installation of such designs on the mosque door. The primary questions of present study are concerned with (a) forms and roles of metal works of art installed on the door of Saheb al-Amr Mosque, and (b) reasons of installing these metallic works of art on the mosque door considering the inhibition of using portraiture in religious places. In order to answer these questions, descriptive-analytical method was adopted. The required information and data of this study were collected through field study and library review. The data analysis method is qualitative and results of this study, following collection of data and its analysis, suggest that the metal works of art were made of low-grade silver and brass by adopting different metalworking techniques which were inspired by contemporary art of Qajar era. The importance of the mosque to the public opinion led to installation of such objects in the mosque since they acted as means of indigent Muslims’ vow fulfilling.